Risk Stratification in Advanced Biliary Tract Cancer: Validation of the A.L.A.N. Score. (23rd June 2020) - Müller, Lukas; Mähringer-Kunz, Aline; Jungmann, Florian; Tanyildizi, Yasemin; Bartsch, Fabian; Czauderna, Carolin; Düber, Christoph; Galle, Peter R.; Weinmann, Arndt; Kloeckner, Roman; Hahn, Felix
Abstract : Background . In addition to the clinical parameters, immune-inflammatory markers have emerged as prognostic factors in patients with advanced biliary tract cancer (ABC). The recently proposed A.L.A.N. score combines both in an easily applicable manner. The aim of this study was to perform the first external evaluation of this score. Methods . All patients from our clinical registry unit who had unresectable ABC underwent first-line chemotherapy from 2006 to 2018 and met the inclusion criteria of the original study were included ( n  =  74). The A.L.A.N. score comprises the following parameters: actual neutrophil count, lymphocyte-to-monocyte ratio, albumin, and neutrophil-to-lymphocyte ratio (A.L.A.N.). Univariate and multivariate hazard regression analyses were performed to evaluate the score's parameters regarding overall survival (OS). The concordance index (C-index) and integrated Brier score (IBS) were calculated to evaluate the score's predictive performance. Results . Low, intermediate, and high A.L.A.N. scores corresponded to median OS of 21.9, 11.4, and 4.3 months, respectively, resulting in a significant risk stratification (log-rank p = 0.017 ). In multivariate analysis, a high-risk A.L.A.N. score remained an independent predictor of poor survival (p = 0 . 016 ). Neutrophil-to-lymphocyte ratio was not a significant factor for poor OS in the analyses in the cohort. The score's ability to predict individual patient survival was only moderate with a C-index of 0.63. Conclusions . The A.L.A.N. score can be used to identify risk groups with a poor prognosis prior to the start of chemotherapy. However, the ability of the score to predict individual patient outcome was only moderate; thus, it may only serve as a minor component in the complex interdisciplinary discussion.